Defects and dilapidation of British Colonial buildings in Negeri Sembilan, Malaysia - Ab Rashid, Nor Syahila; Rashidi, Nur Aisyah Safwa; Abd. Manaf, Azhani (Universiti Teknologi MARA, Perak, 2025)
Colonial buildings in Malaysia play a pivotal role in revealing the nation’s rich history. The advent of British colonisation in the early 19th century not only reshaped the political landscape but also left a lasting imprint on the architectural heritage of the era. However, the passage of time has posed significant challenges to the structural integrity of these heritage structures, with defects progressively compromising their stability. This paper aims to identify specific flaws in two colonial buildings in Negeri Sembilan and propose effective solutions to prevent their deterioration. These buildings were selected as case studies because colonial architecture in Negeri Sembilan has received less attention compared to other prominent Malaysian states, despite the rich collection of British colonial architecture in Seremban. By employing a comprehensive methodology that includes observational studies of these buildings with varied functions and historical contexts, along with interviews with building owners and government officials, this research provides valuable insights into the accumulated defects and strategies for mitigation. The primary causes of these defects were identified as environmental factors, with high humidity, rain exposure, and natural aging being significant contributors. This study underscores the urgent need for systematic maintenance and highlights the importance of conserving these architectural gems, officially recognised as part of our national heritage. Serving as a call to action, this research advocates for collective efforts to ensure the preservation and enduring existence of these invaluable historical assets.